Analysis of Food Security Conditions and Factors Affecting Pond Farmers Using the Approach of Food Consumption Score (FCS) in the Coastal Area of Bangil Subdistrict - Dwi Wulandari; Awang Tri Satria (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2025)
Food security is a basic human need that comes from biological resourcesand water, whether processed or not, for human consumption. Law No.18/2012 states that the fulfillment of food is a human right. This study aimsto assess the food security of pond farmers in the coastal areas of BangilRegency, especially in the villages of Kalianyar, Raci, and Tambakan, andthe factors that influence it. The study used purposive sampling method withdata collection through interviews, observation, and documentation. Foodsecurity was measured using the Food Consumption Score (FCS), and dataanalysis was done descriptively quantitatively and by ordinal logitregression. The results showed that of the total respondents, 20.51% were inthe poor category (low food security), 30.77% were in the borderlinecategory (vulnerable), and 48.72% were in the acceptable category (good).Overall, 79.49% of respondents have good food security, but the rest stillface challenges in meeting their food needs. Significant factors affectingfood security are the number of family members, income and cultivationexperience. A simultaneous test showed a statistically significantrelationship with a p-value of 0.0011. These findings emphasize theimportance of paying attention to vulnerable groups to improve quality oflife and food security.Keywords: Food security, Food Consumption Score, Pond Farmers,Aquaculture, factors